Territoriality drives patterns of fixed space use in Caribbean parrotfishes - Joshua C. Manning; Sophie J. McCoy (Ecology and Evolution, 2023)
Abstract Animals often occupy home ranges where they conduct daily activities. In many parrotfishes, large terminal phase (TP) males defend their diurnal (i.e., daytime) home ranges as intraspecific territories occupied by harems of initial phase (IP) females. However, we know relatively little about the exclusivity and spatial stability of these territories. We investigated diurnal home range behavior in several TPs and IPs of five common Caribbean parrotfish species on the fringing coral reefs of Bonaire, Caribbean Netherlands. We computed parrotfish home ranges to investigate differences in space use and then quantified spatial overlap of home ranges between spatially co‐occurring TPs to investigate exclusivity. We also quantified the spatial overlap of home ranges estimated from repeat tracks of a few TPs to investigate their spatial stability. We then discussed these results in the context of parrotfish social behavior. Home range sizes differed significantly among species. Spatial overlap between home ranges was lower for intraspecific than interspecific pairs of TPs. Focal TPs frequently engaged in agonistic interactions with intraspecific parrotfish and interacted longest with intraspecific TP parrotfish. This behavior suggests that exclusionary agonistic interactions may contribute to the observed patterns of low spatial overlap between home ranges. The spatial overlap of home ranges estimated from repeated tracks of several TPs of three study species was high, suggesting that home ranges were spatially stable for at least 1 month. Taken together, our results provide strong evidence that daytime parrotfish space use is constrained within fixed intraspecific territories in which territory holders have nearly exclusive access to resources. Grazing by parrotfishes maintains benthic reef substrates in early successional states that are conducive to coral larval settlement and recruitment. Behavioral constraints on parrotfish space use may drive spatial heterogeneity in grazing pressure and affect local patterns of benthic community assembly. A thorough understanding of the spatial ecology of parrotfishes is, therefore, necessary to elucidate their functional roles on coral reefs.